Design Analysis of Bicycle Brake Disc for Carbon Fibre - Lightweight Material - Naveed, Nida; Whitford, Michael (International Journal of Integrated Engineering, 2019)
Abstract-Disc brakes are becoming a popular choice on cycles, disc brakes provide greater control of braking application and greater reliability, particularly in wet conditions. The transportation industry has seen many advances in material used over the decades, with the aim of reducing weight whilst maintaining or increasing strength and thermal properties. The study looks at the advantages of the lightweight composite materials used to develop the disc brakes for the bicycle applications with the primary aim of weight reduction. The strength to weight ratio as well as heat dissipation is analysed and compared to brake disc materials already widely used in cycling, therefore the material choice and design of disk is of importance. Research established heat dissipation and strengthening techniques in current use, from this, six designs are created. One of which closely matching a currently available brake disc, the purpose of this is to create a benchmark for the analyses. The three materials identified for the use in the brake disc designs are stainless steel, titanium and carbon fibre. Results showed that significant weight saving can be achieved when using low density material-carbon fibre. Stress (Von Mises) and displacement equalled or improved upon standard stainless steel brake discs. Thermal analysis showed that carbon fibre is able to achieve good levels of heat dissipation, without the need of extra cooling features. It is determined that a road going bicycle brake disc can be up to 70% lighter when carbon fibre is used in conjunction with the design best suited for the material.